Therapeutic Effectiveness of Mirror Therapy Combined with Music Therapy on Upper Limb Motor Function in Hemiplegic Patients with Stroke - SHI Bohan; ZHU Yan; MA Shujie; XU Qian; WANG Ping; CHEN Zhu; ZHU Weijia (康复学报)
ObjectiveTo investigate the therapeutic effect of mirror therapy combined with music therapy on the recovery of upper limb function in hemiplegic patients with stroke.MethodsA total of eighty-one stroke patients with upper extremity dysfunction were included and randomly divided into conventional rehabilitation group，mirror therapy group andcombined treatment group，with 27 cases in each group.All patients received routine physical therapy，drug therapy and nursing. The mirror therapy group received mirror therapy （MT） on the basis of conventional rehabilitation，and the combined treatment group received music therapy combined with MT，additionally. Each group received continuous treatment for four weeks，30 min per day，once a day，and 5 days per week.Before and after four weeks of treatment，their upper limb motor function and ADL were assessed with modified Ashworth scale（MAS） of the upper limb，Fugl-Meyer assessment upper extremity（FMA-UE），modifled Barthel index（MBI），and their motor evoked potential（MEP） latency in affected brain areas were measured.ResultsThere were no significant differences in FMA-UE scores，and MEP latency in the three groups before treatment （P>0.05）.After 4 weeks of treatment，the FMA-UE scores，MBI scores，MAS grade and MEP latency of the three groups were all improved compared with those before treatment（P<0.05）. The FMA-UE scores，MAS grade，MEP latency for the combined treatment group were （35.09±4.11），（51.67±7.31） and （20.89±1.68），which were better than those of the conventional rehabilitation group and the mirror therapy group （P<0.05）；FMA-UE scores，MAS grade，and MEP latency in the mirror therapy group were better than those in the conventional rehabilitation group （P<0.05）. MAS grade of the upper limb of the patients in the combined treatment group was lower than that in the conventional rehabilitation group and the mirror therapy group （P<0.05）；However，there were no significant statistical differences in MAS grade between the mirror therapy group and the conventional rehabilitation group （P>0.05）.ConclusionMirror therapy combined with music therapy can be more effective than mirror therapy alone for promoting the recovery of the upper limb function and the activities of daily living，also for alleviating the upper limb spasticity and improving the excitability the motor cortex of the affected brain area.